Galaxy evolution with FMOS - Curtis Lake, E (2010)
This thesis is concerned with the targeting of emission line galaxies with FMOS (Fibre Multi-Object Spectrograph) to determine properties of star forming galaxies at redshift ~1.5, and provide measurements of the growth rate of large-scale structure through Redshift Space Distortions (RSDs). I also consider the opportunities of targeting the passive galaxy population at high redshift, through measurements of their continuum. I start with the extensive broad-band photometric data available in the UKIDSS-UDS (United Kingdom Infrared Telescope Deep Sky Survey - Ultra-Deep Survey) field which is used to produce a band-merged catalogue, later used for determining photometric redshifts. In producing this catalogue, I approach the issue of source confusion present in the deep Spitzer imaging using z-band priors on profile position and shape and an iterative Expectation-Maximisation algorithm. Photometric redshift estimates are compared against colour selections as potential targeting techniques for a wide-area redshift survey with FMOS. Different photometry survey areas are considered, and the quality of selection given the available broad-band data tested, by adjusting the photometric catalogue produced for the UDS. The results indicate that the SWIRE (Spitzer Wide area InfraRed Extragalactic Survey) fields are too small to provide adequate sources with a consistent selection mechanism. The CFHTLS (Canada-Frace-Hawaii Telescope Legacy Survey) would have a large enough area given deeper z'-band imaging, and SWIRE-depth coverage in the Spitzer 3.6μm and 4.5μm bands. I present FMOS commissioning data obtained for the UDS field, including the spectroscopic targeting of sources form the High-Z Emission Line Survey (HiZELS). With this data, I am able to test the current quality of flux calibration using cool stars targeted simultaneously and the level of systematic errors left by sky-subtraction. The sample of HiZELS sources selected to place Hα at z~1.45 show low contamination from other emission lines, and only one out of 9 targets assigned a redshift has any indication of AGN activity. Finally, I present longslit observations of faint, passive galaxies at redshift z~1.9, selected as members of a possible cluster, JKCS 041, selected from broad band colours. One object was observed with high enough signal to noise to constrain the position of the 4000 Å / Balmer break, providing a tighter constraint on the photometric redshift of 1.8867 +0.0034 -0.0117.